2012
DOI: 10.1098/rsbl.2012.0151
|View full text |Cite
|
Sign up to set email alerts
|

When it is costly to have a caring mother: food limitation erases the benefits of parental care in earwigs

Abstract: The aggregation of parents with offspring is generally associated with different forms of care that improve offspring survival at potential costs to parents. Under poor environments, the limited amount of resources available can increase the level of competition among family members and consequently lead to adaptive changes in parental investment. However, it remains unclear as to what extent such changes modify offspring fitness, particularly when offspring can survive without parents such as in the European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 16 publications
4
61
0
Order By: Relevance
“…[4,28]). Previous studies already revealed that the maternal presence reduces nymph survival when families had restricted food access [21], but increased nymph survival when families had access to low quality food [15]. Here, the effects of maternal presence under ad libitum, high quality food could reveal an increased expression of sibling rivalry when juveniles have access to maternal resources, as proposed in a recent model [29].…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…[4,28]). Previous studies already revealed that the maternal presence reduces nymph survival when families had restricted food access [21], but increased nymph survival when families had access to low quality food [15]. Here, the effects of maternal presence under ad libitum, high quality food could reveal an increased expression of sibling rivalry when juveniles have access to maternal resources, as proposed in a recent model [29].…”
Section: Discussionmentioning
confidence: 50%
“…Under our experimental conditions, these effects did not translate into the production of high quality nymphs by maternally-deprived females, as we found no parent-of-origin effect of maternal loss on the mean weight and survival rate of these nymphs. However, the accelerated developmental time of the offspring of maternally-deprived females could be indicative of parent-of-origin effects that increase the level of sibling rivalry among these offspring [15,21]. On a proximate level, the transgenerational effects of maternal loss on nymph defence could be mediated by a parent-of-origin effect on the offspring's chemical signatures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations